2021
DOI: 10.1212/con.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorders

Abstract: PURPOSE OF REVIEW This article describes the phenomenology and clinical presentation of obsessive-compulsive disorder (OCD), a common but underdiagnosed psychiatric disorder. Guidance for effectively identifying obsessive-compulsive symptoms is provided, and treatment options, including psychotherapy, pharmacologic management, and neuromodulation approaches for treatment-resistant OCD, are discussed. RECENT FINDINGS OCD affects 2% to 3% of adults worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…Depression and anxiety symptomatology were used as criteria because their comorbidity with OC symptoms is well established [ 11 , 14 , 40 , 41 , 42 ]. It is known that mothers’ depression severity is positively related to various aspects of intrusive thoughts’ severity and interference [ 10 , 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression and anxiety symptomatology were used as criteria because their comorbidity with OC symptoms is well established [ 11 , 14 , 40 , 41 , 42 ]. It is known that mothers’ depression severity is positively related to various aspects of intrusive thoughts’ severity and interference [ 10 , 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until the development of the Perinatal Obsessive–Compulsive Scale (POCS) [ 17 ], the study of OCD in this period was hampered by the absence of a specific instrument. Because of the egodystonic nature of these infant-related intrusive thoughts, feelings of guilt and shame and the associated stigma, it is very rare for women to spontaneously report these symptoms, which are underdetected and undertreated [ 18 ], and may predispose to the development or exacerbation of OCD in vulnerable individuals [ 11 ]. These factors have led to recent calls for further screening of ppOCD in the postpartum period and the development of measures for this purpose [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It typically manifests as a chronic condition and often exists with comorbidities, responds partially to treatment, leading to significant impairment. 1,2 A large network meta-analysis evaluating the efficacies of psychotherapeutic interventions and pharmacotherapies in OCD has revealed that the serotonergic medications, including selective serotonin reuptake inhibitors and clomipramine, exhibit similar efficacy, while the combination of pharmacological and psychotherapeutic interventions are more effective than individual treatment modalities. 3 After the initiation of treatment with serotonergic medications, significant clinical improvements can be observed (in comparison to placebo) within the initial 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Obsessive-compulsive disorder (OCD) is a prevalent mental illness, affecting approximately 2%–3% of the population. It typically manifests as a chronic condition and often exists with comorbidities, responds partially to treatment, leading to significant impairment 1 , 2 . A large network meta-analysis evaluating the efficacies of psychotherapeutic interventions and pharmacotherapies in OCD has revealed that the serotonergic medications, including selective serotonin reuptake inhibitors and clomipramine, exhibit similar efficacy, while the combination of pharmacological and psychotherapeutic interventions are more effective than individual treatment modalities 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation